TIPOLOGI PENERAPAN KONSEP KAWASAN BERBASIS TRANSIT DI 11 STASIUN KOTA KECIL JALUR SELATAN PULAU JAWA - Priambodo, Danang; Muhammad Sani Roychansyah (Program Studi Arsitektur Institut Teknologi Nasional (ITN) Malang, 2025)
The transportation system in Indonesia, particularly railways, is developing quite well. Trains have become the preferred mode of long-distance travel due to their efficiency and affordability. The improvement in transportation systems has influenced railway stations to become hubs of movement and catalysts for urban development in their vicinity. In Indonesia, the concept of Transit-Oriented Development (TOD) is being implemented in several major cities along railway lines, and there are plans to extend it to small towns with stations along the southern route of Java Island. This initiative marks the beginning of regional development, especially around these stations. This research combines qualitative and quantitative methods to analyze the characteristics of stations in small towns along the southern route of Java Island and assess the application of the 5D attributes of TOD concept. The analysis results indicate that the TOD area development concept at 11 small-town stations along the southern route of Java Island still requires adjustments. The application of 5D TOD attributes in these suburban areas is still low, particularly concerning pedestrian walkway design, transit access, and influential station locations. For example, despite needing improvement, Ciamis Station has better transportation access and transit points due to its proximity to Bandung City.